Shear Bond Strength of the Repair Composite Resin to Zirconia Ceramic by Different Surface Treatments - Arami, Sakineh; Hasani Tabatabaei, Masoumeh; Namdar, Fatemeh; Safavi, Nassimeh; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2014)
Introduction: The purpose of this study is the evaluation of the amount of surface roughness (Ra) of Zirconia Ceramic following different surface treatments as well as the assessment of its shear bond strength to composite resin. Methods: 40 sintered zirconia ceramic block samples were randomly divided in 4 groups of 10 and underwent the following surface treatments: a) Control group without treatment b) Air abrasion with Al2O3 particles (50um) c) Er:YAG laser with 2W power for 10s d) Nd:YAG laser with 1.5W power for 2min Then the mean surface roughness (Ra) was evaluated by profilometer. In the next step, Alloy primer was used on a section of 9mm2 on the samples following the manufacturer’s instructions. After that Clearfil AP-X composite resin in cylinder shape with an internal diameter and height of 3mm were cured on the sections mentioned. At the end, all samples were tested to assess the shear bond strength by the Universal Testing Machine at a speed of 0.5mm/min until fracture occurred. The mean shear bond strengths were calculated and statistically analyzed by One Way ANOVA. Results: ANOVA analysis showed that roughness (Ra) was significantly different between the groups (P≤0.05). Ra was higher in the Nd:YAG group compared to the other groups (P≤0.05). The lower Ra was related to the control group. Air abrasion group showed highest amounts of shear bond strength and Nd:YAG laser group demonstrated lower amounts of shear bond strength (P≤0.05). Conclusion: Various surface treatments are differently effective on bond strength. Air abrasion is the most effective method to condition zirconia ceramic surfaces.